Postoperative Complications in Patients Undergoing Minimally Invasive Sacroiliac Fusion. Issue 1 (April 2016) - Schoell, Kyle; Buser, Zorica; Jakoi, Andre; Pham, Martin; Patel, Neil; Liu, John; Hsieh, Patrick; Wang, Jeffrey C.
Introduction: Minimally invasive sacroiliac (SI) fusion has become increasingly popular as a treatment for non-traumatic sacroiliac joint pain in recent years. This has created significant need for reliable data addressing risks associated with the procedure. Initial investigations have focused primarily on efficacy and patient satisfaction with small sample size. Furthermore, the majority of past studies have been primarily single center or case series investigations and as such their findings were limited to their sample populations. The aim of this study was to analyze complications associated with minimally invasive SI fusion using a large medical record database that more closely and accurately models the American population as a whole. Material and Methods: Patients undergoing minimally invasive SI fusion from 2007–2014 were selected from records of the nationwide private insurance provider Humana. Using the Pearl Diver patient records database (Pearl Diver Technologies, West Conshohocken, PA, USA), patient data on age, procedure date, and medical diagnoses before and after the procedure was acquired. ICD-9 diagnosis codes (International Classification of Diseases 9 th edition) were used to reveal incidence of post-operative complications including infection, pain, osteomyelitis, joint derangement, uterine tract infection (UTI), and nerve pathology. Cases of pre-existing conditions were excluded from the analysis. The data was also examined for incidence of patients with diagnoses of new lumbar pathology following the procedure. Patients undergoing SI fusion for surgical revision, neoplasia, or pelvic ring trauma were excluded from the study. Results: Data from 469 patients (305 female; 164 male) showed a substantial increase in the number of minimally invasive sacroiliac fusion procedures performed from 2007–2014 [ p < .05]. Among these patients, an overall complication rate of 13.2% was seen at 90 days and 16.4% at 6 months post-op. Rates of individual complications were as follow. Infection: 30 days = 3.0%, 90 days = 3.6%, 6 months = 4.1%. Pain: 90 days = 2.6%, 6 months = 4.1%. UTI: 90 days = 3.8%, 6 months = 4.9%. Nerve pathology: 90 days = 4.3%, 6 months = 6.2%. Incidence of novel lumbar pathology was 3.6% at 90 days post-op and 5.3% at 6 months. Males experienced diagnoses of novel lumbar pathology at higher rates than females at both 90 days (M=6.7%; F≤3.3%) and 6 months (M=9.1%; F≤3.3%) [ p < .01]. Conclusion: The results of this study show that minimally invasive SI joint fusion may carry higher risks of complications than previously stated, including a possible association with the development of lumbar pathology. These finding are critical for physicians and patients considering minimally invasive SI fusion as a treatment for chronic SI joint pain, and should be taken under careful consideration when deciding if surgical treatment is warranted.